2013
DOI: 10.1108/01409171311315003
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of corporate governance practices of Islamic banks versus Islamic bank windows of conventional banks

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 34 publications
(45 reference statements)
0
7
0
3
Order By: Relevance
“…In case of Islamic banking no consensus have found regarding the BS and firm performance e.g. Grassa and Matoussi (2014), Quttainah (2013) and Shahzad Bukhari et al (2013) found positive relationship between BS and performance and Mollah and Zaman,(2015), Bukair and Rahman (2015) found negative relationship, whereas Grassa et al (2010) and Juras and Hinson (2008) found no association.…”
Section: Literature Review and Formulation Of Hypothesesmentioning
confidence: 99%
“…In case of Islamic banking no consensus have found regarding the BS and firm performance e.g. Grassa and Matoussi (2014), Quttainah (2013) and Shahzad Bukhari et al (2013) found positive relationship between BS and performance and Mollah and Zaman,(2015), Bukair and Rahman (2015) found negative relationship, whereas Grassa et al (2010) and Juras and Hinson (2008) found no association.…”
Section: Literature Review and Formulation Of Hypothesesmentioning
confidence: 99%
“…Banks manage the funds of different account holders and investors and such activities of banks make it more important to emphasis on corporate governance in a greater extent than other corporate bodies because any delinquency from the bank side may have confrontational effect on its stakeholders and may conceivably stimulate the rise to agency issues and conflict of interest between the management and those who have exposed their faith in banking with the banks for superior management of their funds. Understanding the importance of corporate governance, many countries have established their own codes of conduct for effective corporate governance based on some common issues applicable throughout the world along with some country specific characteristics (Shahzad, Awan and Ahmed, 2013;Dincer & Kilinç 2018).…”
Section: Introductionmentioning
confidence: 99%
“…DPS dianggap efektif ketika DPS mampu meningkatkan legitimasi Syariah bank Syariah. Adapun Bukhari, Awan, & Ahmed (2013) dan Firdausi & Sulung (2019) memaparkan metode pendekatan sumber (resource approach) yang menghubungkan efektivitas organisasi dengan faktor input personal atau kualitas, kriteria, dan karakteristik personal anggota organisasi sebagai alternatif cara pengukuran efektivitas kinerja suatu organisasi. Hal itu senada dengan pendapat Verriest, Gaeremynck, & Thornton (2013) yang menyatakan bahwa efektivitas kinerja DPS diukur dengan indeks agregat yang disusun berdasarkan karakteristik DPS.…”
unclassified